Mechanics of additive and advanced manufacturing. proceedings of the 2018 Annual Conference on Experimental and Applied Mechanics /: proceedings of the 2018 Annual Conference on Experimental and Applied Mechanics. Volume 8 : ([2019]) - Unknown
No abstract available